Great Powers and Strategic Stability in the 21st Century : Competing Visions of World Order - Edited By Graeme P. Herd. (New York Routledge Taylor and Francis Group, 2010)
This book addresses the issue of grand strategic stability in the 21st century and examines the role of the key centres of global power - America, the European Union, Russia, China and India - in managing contemporary strategic threats.
Includes Index, Bibliography and Illustrations.
"Geneva Center for Security Policy."
Keywords: Security, International -- World Politics -- Great Powers